THE IMPACT OF UNEMPLOYMENT ON SUBSTANCE ABUSE: A STUDY ON THE YOUTH OF KASHMIR - Mohd Arif Naikoo; Aamer Nabi Ganaie (RADJA PUBLIKA, 2023)
This study examines the relationship between unemployment and substance abuse among the youth of Kashmir. Given the region's complex socio-political environment, high unemployment rates, and increasing reports of substance abuse, it is crucial to understand the underlying dynamics. Through a mixed-methods approach, this research aims to provide a comprehensive analysis of how unemployment contributes to substance abuse among Kashmiri youth and to suggest potential